Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai dengan Kompetensi sebagai Variabel Moderating pada UPTD Puskesmas Kayu Gadang - Yulianti, Tuti (Lembaga Yasin AlSys, 2026)
This study aimed to analyze the effects of work discipline and work motivation on employee performance, with competence as a moderating variable, at the UPTD Puskesmas Kayu Gadang, Pesisir Selatan Regency. A quantitative approach with an explanatory research design was employed, involving a population of 64 employees, all of whom were included as the sample using a saturated sampling technique. Data were collected through a closed-ended questionnaire using a five-point Likert scale and were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the aid of SmartPLS software. The results showed that work discipline had a positive and significant effect on employee performance, whereas work motivation did not have a significant effect on employee performance and, in fact, exhibited a negative direction of association. The moderating variable test indicated that competence significantly strengthened the effect of work discipline on employee performance but did not strengthen the effect of work motivation on employee performance. These findings suggest that improving the performance of primary health care staff is more effectively achieved by reinforcing work discipline supported by adequate competence, and they provide empirical contributions to the development of human resource management in the primary health care service sector.